Long-term neurological outcomes in patients after out-of-hospital cardiac arrest. (April 2016) - Kim, Youn-Jung; Ahn, Shin; Sohn, Chang Hwan; Seo, Dong-Woo; Lee, Yoon-Seon; Lee, Jae Ho; Oh, Bum Jin; Lim, Kyoung Soo; Kim, Won Young
Abstract: Aim: The main treatment goal in survivors of out-of-hospital cardiac arrest (OHCA) is a favorable neurologic outcome. Little is known, however, about long-term trends of neurologic status in OHCA survivors. This study was designed to assess the rates of long-term neurologic recovery and survival according to neurologic status at one month. Methods: This retrospective observational study assessed all adult OHCA survivors (≥18 years) admitted to a tertiary hospital in an urban area who achieved return of spontaneous circulation (ROSC) between July 2005 and August 2013. Neurologic outcomes were measured by Cerebral Performance Category (CPC) score and patients were categorized according to CPC score at 1 month. Their neurologic status was re-evaluated 6, 12, and 24 months after cardiac arrest. Results: Of 778 OHCA cases, 282 patients (36.2%) were admitted to our hospital, and 279 were included in this study. At one month, 84 (30.1%) survivors were assessed with the CPC with 42.8% ( n = 36) having good neurologic outcome and 57.1% ( n = 48) poor neurologic outcome. Only two patients with poor neurologic outcome (4.1%) showed improved neurologic status from CPC 3 to CPC 2, during the first 6 months and none showed neurologic improvement after 6 months. The estimated 3-year survival was much higher for CPC 1 (96.4%) than for CPC 4 (24.2%) survivors. Conclusions: Neurologic recovery of OHCA survivors with poor neurologic outcomes at one month was rare and did not occur more than 6 months after cardiac arrest.